(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Everyone in this globe wants to become happy in one’s life. But very few becomes successful in doing so. On careful pondering it is apparent that it is possible only after the acquisition of physical, mental, social and spiritual well being. One of the obstacles in attaining it is non-communicable diseases. Available country-level evidence indicates that these diseases pose a tremendous economic burden that can be felt far beyond the health sector. In fact, according to the World Economic Forum’s annual risk report, non-communicable diseases have been determined a major risk to economic loss by global business leaders and decision makers. The efforts made by Government of India and the States have not been able to check rising burden of non-communicable diseases owing to limited scale of implementation. There is an urgent need for a comprehensive scheme that should focus on health promotion and prevention of these diseases and their risk factors at various levels across the country. Ayurveda, the most ancient Indian healing science, describes a lot of measures to prevent and manage diseases like these. Achara Rasayana is one amongst these measures, which is a code of conduct helpful in attaining a healthy and disease-free living. This article details the various aspects of this priceless measure capable of reducing the Health Budget considerably in the interest of national prosperity.